Global climate financial risk - Sari, Eva Roslina (Institute for Advanced Science Social, and Sustainable Future, 2024)
Climate change poses a major threat to long-term growth and prosperity and has a direct impact on the economic well-being of all countries. Extreme events cost US143 billion per year due to climate change. The majority (63%) of this number is due to the loss of human life. Losses resulting from no action on climate change to the world economy could reach US178 trillion in 2070. Benefits from accelerating the transition to net zero are US43 trillion in the next 50 years, so climate-related financial risk management must be carried out as optimally as possible in industrial groups in the financial sector and non-financial groups. The World Economic Forum reports that climate action failure will dominate the next decade. To achieve financial stability, a strategy is needed through four main aspects: governance, strategy, risk management, and metrics and targets. The scenario that must be targeted is an orderly scenario to achieve global climate mitigation and adaptation targets. The transition to the new climate economy must be carried out by measuring predetermined indicators, as is done by the IMF. Mitigation indicators include environmental taxes, environmental protection spending, renewable energy, low-carbon technology trade, and forests and carbon. Adaptation indicators include carbon taxes, climate finance, the primary energy mix, fossil fuel prices, and the final energy mix.